Consequences of Fraud Factors on Accounting Fraud of Regional Apparatus - Sabaruddinsah, Sabaruddinsah; Asiah , Neng (Lentera Ilmu Nusantara, 2024)
The purpose of this study is to understand the influence of compensation suitability, money ethics, and internal control systems on accounting fraud committed by local officials. This research was conducted with a quantitative descriptive approach using a correlation approach, and samples were taken using a sampling technique by criteria. Data for this study was collected through filling out a questionnaire distributed to staff members of the Regional Work Unit (SKPD). The SmartPLS (Partial Least Square) program is used to model the data to be analyzed. The study found that money ethics had a positive effect, while the internal control system and the appropriateness of compensation had a negative effect on accounting fraud among regional officials.